Preparedness for Flood Disasters: A Scoping Review - Manurung, Sherly; Nurjanah, Evi; Iqbal, Muhammad; Meilando, Rizky; Nuraen, Aan; Ricky, Denny (11th International Scholars Conference, 2024)
Extreme weather occurs in various parts of the world which causes natural disasters. Floods are the most frequent disasters and have the most impact both on life and the economy on a large scale. The purpose of this study is how the preparedness for flood disaster management. This study uses the Scoping Review research method. Data search through database sources, namely PubMed, ProQuest, CINAHL and Google Scholar. Keywords: Disaster Preparedness AND Community AND Flood Disaster. The literature selection used the PRISMA approach by identifying duplicate articles, inappropriate titles, inappropriate abstracts and with inclusion criteria, namely articles with published years from 2015 to 2021 in English and full text form. Only 22 articles met the inclusion criteria. Data were analyzed qualitatively with the help of data extraction tables and arranged thematically based on content analysis. These findings indicate that flood disaster preparedness management involves various parties, namely from local government policies and authorities as well as public awareness. Then we need tools to be able to provide fast and precise information such as early warning systems and the use of social media technology for flood risk assessment. It was found from the demographic data of the population in the flooded area, that household disaster preparedness is very low, so it is necessary to provide training to the community on disaster preparedness to increase the knowledge and skills of residents so that they can build a resilient community in preparation for disaster. It is expected that flood disaster management preparedness involves various parties, such as the central government and local communities, as well as various multi-disciplinary sciences.